Representation of sentence meaning (A JNLE Special Issue). (July 2019) - Bojar, Ondřej; Bernardi, Raffaella; Webber, Bonnie
Abstract: This paper serves as a short overview of the JNLE special issue on representation of the meaning of the sentence, bringing together traditional symbolic and modern continuous approaches. We indicate notable aspects of sentence meaning and their compatibility with the two streams of research and then summarize the papers selected for this special issue.